The Contradiction of Obesity Incidence Based on Sleep Duration in Adolescents - Maritasari, Dwi Yulia; Baharza, Satria Nandar; Listina, Febria (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Obesity is an abnormal state of excess body fat where obesity that occurs in adolescence increases the risk of obesity as an adult and causes several health problems. This study aims to differ the proportion of obesity incidence based on sleep duration in high school adolescents in the Tanah Abang District, Central Jakarta. The study design was cross sectional, sampling using the simple random sampling method, and a total sample of 100 students. Data analysis included univariate and bivariate analysis with chi-square tests. The results showed that respondents categorized as obese based on Body Mass Index (BMI) were 37 (37 percent) adolescents, and respondents categorized as obese was based on Body Fat Percent (PLT) of 32 (32 percent) adolescents. There is a difference in the proportion of obesity incidence based on sleep duration in adolescents (p value = 0.003, OR = 5.79). Adolescents should improve their sleep patterns according to the recommended duration to prevent obesity, which is at least 7 hours a day. ABSTRAKObesitas merupakan keadaan kelebihan lemak tubuh yang abnormal dimana obesitas yang terjadi pada masa remaja meningkatkan risiko obesitas saat dewasa dan menimbulkan beberapa masalah kesehatan. Penelitian ini bertujuan perbedaan proporsi kejadian obesitas berdasarkan durasi tidur pada remaja SMA di Kecamatan Tanah Abang Jakarta Pusat. Desain penelitian adalah cross sectional, pengambilan sampel menggunakan metode simple random sampling, dan total sampel sebanyak 100 siswa. Analisis data meliputi analisis univariat dan bivariat menggunakan uji statistik chi-square. Hasil penelitian menunjukkan bahwa responden yang dikategorikan obesitas berdasarkan Indeks Massa Tubuh (IMT) sebanyak 37 (37 persen) remaja, dan responden yang dikategorikan obesitas berdasarkan Persen Lemak Tubuh (PLT) sebanyak 32 (32 persen) remaja. Ada perbedaan proporsi kejadian obesitas berdasarkan durasi tidur pada remaja (pvalue = 0,003, OR = 5,79). Sebaiknya remaja memperbaiki pola tidur sesuai dengan durasi yang dianjurkan agar mencegah terjadinya obesitas yaitu minimal 7 jam sehari.